FRI0095 Anti-tnfΑ versus rituximab in refractory peripheral ulcerative keratitis associated to rheumatic diseases. multicenter study of 24 patients. (12th June 2018) - Domínguez Casas, L.C.; Calvo-Río, V.; Maíz-Alonso, O.; Blanco, A.; Beltran, E.; Martinez Acosta, L.; Alvarez de Buergo, M.C.; Rubio-Romero, E.; Díaz-Valle, D.; López-González, R.; García- Aparicio, A.; Juan Mas, A.; et al.
Abstract : Background: This study shows that treatment with biologic drugs, including ant-TNF drugs, in NION associated to IMIDs, refractory to conventional treatment, seems to be effective. These results must be confirmed in prospective and randomised trials. Objectives: Our aim was to compare anti-TNFα vs Rituximab (RTX) in refractory PUK. Methods: Multicenter study of 24 patients with PUK. All of them presented inadequate response to corticosteroids and at least 1 systemic traditional immunosuppressive drug. Anti-TNFα were used in 17 patients: Adalimumab (n=9) 40 mg/sc every 1–2 weeks, infliximab (IFX) (n=7) 3–5 mg/kg iv/4–6 weeks, etanercept (n=1) 50 mg/week. RTX was used in 7 patients 1–2 g i.v. every 6 or 12 months. The main outcomes were Best Corrected Visual Acuity (BCVA), signs of inflammation (scleritis and episcleritis), progression to corneal thinning, central keratolysis and ocular perforation. Results: We studied 24 patients/32 affected eyes. The underlying diseases in the anti-TNFα group were Rheumatoid Arthritis (RA) (n=14), Psoriatic Arthritis (n=2) and Behçet Disease (n=1); and in the RTX group: RA (n=5), granulomatous polyangiitis (n=1) and microscopic polyangiitis (n=1). At baseline there were no significant differences between both groups in general features or in ocular involvement ( table 1). Before biologic therapy they had received the following systemic drugs (anti-TNFα vs RTX) i.v. methylprednisolone (2 vs 4), doxycycline (7 vs 1), ascorbic acid (2 vs 0), MTX (11 vs 4), AZA (1 vs 2) and others (7 vs 3). In addition, 10 patients, in both groups, had required surgery: amniotic membrane (n=5), penetrating keratoplasty (n=2), conjunctival resection (n=2), tissue adhesives (n=2), conjunctival flap (n=1) and lamellar keratoplasty (n=1). Once the treatment was initiated the ocular outcome was similar (table 1). After a mean follow-up of 22.53±22.60 (anti-TNFα) and 22.28±8.28 months with RTX the following severe side effects were observed: supraventricular tachycardia (n=1) with RTX and pulmonary tuberculosis (n=1) with IFX. Conclusions: In this study, anti-TNFα therapy and RTX were equally effective for the treatment of peripheral ulcerative keratitis associated to rheumatic diseases refractory to conventional treatment. Disclosure of Interest: None declared